Therapeutic effects of intensive inpatient rehabilitation in advanced Parkinson's disease. Issue 1 (5th September 2016) - Kaseda, Yumiko; Ikeda, Junko; Sugihara, Katsunobu; Yamawaki, Takemori; Kohriyama, Tatsuo; Matsumoto, Masayasu
Abstract: Background: The importance of rehabilitation therapy in Parkinson's disease is well recognized. However, the effects of an inpatient rehabilitation program for advanced Parkinson's disease have not been fully investigated. Aim: To assess the effects of intensive inpatient rehabilitation. Methods: We enrolled 31 patients (mean age 69.5 ± 9.4 years; mean disease duration 8.8 ± 6.4 years) with advanced Parkinson's disease, without severe cognitive impairment. The median Hoehn–Yahr stage was IV. Patients received 2 h of individualized rehabilitation for 6–7 days each week for 1 month. At hospital discharge, patients and caregivers were instructed to continue daily exercise. Results: Motor and total scores of Functional Independence Measures significantly improved between admission and discharge in patients with stage III and IV disease, but not stage V. There was no significant effect of Hoehn–Yahr stage on improvements in Unified Parkinson's Disease Rating Scale scores, (total, part I, II or III), cognitive Functional Independence Measures or Berg Balance Scale. Conclusion: Intensive inpatient rehabilitation was effective even in advanced Parkinson's disease. Intensive inpatient rehabilitation, together with home and day‐care exercise, might counteract the progressive motor decline in Parkinson's disease.